Answer:
Step-by-step explanation:
6ab²+4a²b-3ab²+3a²b-2a²b²
= 4a²b+3a²b-3ab²+6ab²-2a²b² . . . commutative property of addition (twice)
= (4+3)a²b+(-3+6)ab²-2a²b² . . . . . . distributive property (twice)
= 7a²b+3ab²-2a²b²
_____
We have attempted to correct what we perceive to be typographical errors in the presentation of the problem. As written, you can't get to the second expression from the first, and the first expression doesn't match what you say you're trying to simplify.
Answer: You can travel 43 miles
Step-by-step explanation:
To determine how far you can travel from the airport by taxi for $31.50, we can subtract the fixed charges from the total cost and then divide the remaining amount by the cost per mile.
Let's calculate:
$31.50 - $4.00 (base fare) - $6.00 (airport charge) = $21.50
Now, we can divide the remaining amount by the cost per mile:
$21.50 / $0.50 per mile = 43 miles
So, you can travel approximately 43 miles from the airport by taxi for $31.50.
For any value of x, h(x) will always be greater than g(x).
g(x) > h(x) for x = -1.
g(x) < h(x) for x = 3.
For positive values of x, g(x) > h(x).
For negative values of x, g(x) > h(x).
Answer: g(x) > h(x) for x = -1.
For positive values of x, g(x) > h(x).
For negative values of x, g(x) > h(x).
Step-by-step explanation:
Given functions: and
When x=0, and
∴ at x=0, g(x)=h(0)
Therefore the statements "For any value of x, g(x) will always be greater than h(x)." and "For any value of x, h(x) will always be greater than g(x)." are not true.
When x=-1, and
∴g(x) > h(x) for x = -1. ......................(1)
When x=3, and
∴ g(x) > h(x) for x = 3....................(2)
⇒g(x) < h(x) for x = 3. is not true.
From (1) and (2),
For positive values of x, g(x) > h(x).
For negative values of x, g(x) > h(x).